The Complexity of Washback Effect on Students’ Learning in Toefl Preparation Course - Tetty Novitasari Simbolon (Syntax Corporation, 2022)
English language tests in Indonesia have been long established to measure English language proficiency, especially in higher education. Unlike the huge demand for English competency and the high number of language test takers, research on the washback effect or the effect of tests on language teaching and learning is still limited. This research aims to explore the washback effect found in student learning. This research uses a qualitative research design involving seven final year students from one university in Pontianak as participants. Researcher collected data through classroom observation and interview. This research focused on one type of English test, namely the TOEFL (Test Of English as a Foreign Language). The data collected was used to answer the nature of the TOEFL preparation course and a real picture of all the activities that occured during the learning process. The findings showed that there was a significant effect of the TOEFL and TOEFL preparation course on student learning experience specifically on the depth of learning. Despite the finding that TOEFL preparation course brought positive washback effect on students’ learning, this research suggests higher education institution and teachers to keep providing better teaching and learning experience in test-oriented English class.